1988
DOI: 10.1002/cne.902670206
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of cells projecting to thalamus vs. Those projecting to cerebellum in subdivisions of the dorsal column nuclei in raccoons

Abstract: To learn the distribution of cells projecting to the thalamus, as opposed to the cerebellum, in the mechanosensory nuclei of the dorsal medulla of raccoons, we analyzed the retrograde transport of horseradish peroxidase from the ventrobasal complex of the thalamus and from the cerebellum. We found six nuclear regions projecting heavily to the thalamus with very small projections to the cerebellum: Bischoff's, central cuneate, central gracile, rostral cuneate, rostral gracile nuclei, and cell group z. Two regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 41 publications
1
11
0
Order By: Relevance
“…We also report a distinct dorsal‐medial cell group at the caudal extent of the gracile nucleus that may be an example of Bischoff's nucleus. Bischoff's nucleus is a DCN found in some animals and is often associated with the representation of the tail (Johnson et al, ; Ostapoff and Johnson, ; Sarko et al, ). However, sea lions have diminutive tails, so it is surprising to find such a distinct cell group.…”
Section: Discussionmentioning
confidence: 99%
“…We also report a distinct dorsal‐medial cell group at the caudal extent of the gracile nucleus that may be an example of Bischoff's nucleus. Bischoff's nucleus is a DCN found in some animals and is often associated with the representation of the tail (Johnson et al, ; Ostapoff and Johnson, ; Sarko et al, ). However, sea lions have diminutive tails, so it is surprising to find such a distinct cell group.…”
Section: Discussionmentioning
confidence: 99%
“…The principal somatosensory brainstem nuclei for the manatee include the trigeminal, cuneate, gracile, and Bischoff's nuclei. Bischoff's nucleus, a distinct group of cells in the midline of the caudal medulla (Johnson et al, 1968), has not been identified previously in the manatee but has been shown, along with the cuneate and gracile nuclei, to project heavily to the ventroposterior thalamus (VP) in the raccoon (Ostapoff and Johnson, 1988). In the raccoon, the tail representation occupies the dorsal portion of VP, whereas the hindlimb representation occupies the ventral portion (Johnson et al, 1968).…”
Section: Discussionmentioning
confidence: 99%
“…The somatosensory brainstem nuclei of interest for the manatee include Bischoff's nucleus, the cuneate–gracile complex, and the trigeminal nucleus (in particular, the principal sensory component). Bischoff's nucleus is a distinct group of cells in the midline of the caudal medulla that projects heavily to the ventrobasal thalamus in the raccoon (Johnson et al, 1968; Ostapoff and Johnson, 1988) and constitutes the tail representation in most mammals with a well‐developed tail (Kappers and Ubbo, 1960). By analogy, Bischoff's nucleus would represent the fluke in the manatee and might occupy a disproportionately large area compared with other species due to the tactile hairs present on the fluke.…”
mentioning
confidence: 99%
“…1). In this study we included the cell clusters devoted to the tail in the gracile nucleus, although others have distinguished this cell group as Bischoff's nucleus (Kappers et al, 1936;Johnson et al, 1968;Ostapoff and Johnson, 1988). By injecting compounds that were transported from the skin to the terminations of cutaneous afferents in the gracile nucleus, we were able to determine where in the gracile nucleus afferents from different body parts terminate in the four primates studied.…”
Section: Resultsmentioning
confidence: 99%